ENHANCING LOYALTY: IMPROVING THE EXPERIENCE QUALITY OF INDONESIAN FOOTBALL CLUB FANS - Rohman, Fatchur (Universitas Brawijaya, Indonesia, 2019)
The high income generated by the sports industry, making this industry one of the industries that had a high level of competition. The sports industryuniqueness is the high participation of supporters in creating value services that are thought to satisfy and increase the loyalty of supporters. This research was conducted with the aim to analyze how the influence of the quality of the experience of the results of the participation of supporters in sports activities, especially football on the loyalty of these supporters. Two hundred fifty samples were collected using purposive sampling technique. The data obtained is then processed using the SmartPLS 3.0 application. The results showed that to increase the loyalty of sports club supporters,need to pay attention to the club’s image and supporter satisfaction because both of these variables have a mediating role to the relationship between the quality of the supporter’s experience and supporter loyalty. Based on the results of the study, in addition to improving the quality of sports team management experience, it is also necessary to maintain the club’s image and supporter satisfaction to increase supporter loyalty.